Dinamika Sistem Penghidupan Masyarakat Tani Tradisional dan Modern di Jawa Barat - Ita Mardiyaningsih, Dyah; Hadi Dharmawan, Arya (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2010)
The Green Revolution is known as one of modernization approaches in Indonesia. Based on many research in Java, Green Revolution has made changes in rural, sociologically, economically and ecologically. Even though, there are still also some villages which are not experiencing this change. Some communities are still hold the indigenous social institutional system as the directional guidance of their community livelihood system. The research is applying qualitative approach with the use of case study and socio-historical strategy to learn how much the indigenous rural social institutional system is able to guarantee the community livelihood system? To learn this subject, the research has conducted in Kasepuhan Sinar Resmi (Sukabumi) and Dusun Sumurjaya (Subang). The research it self is applying perspective of Mazhab Bogor which sees the rural community livelihood system character in four aspects: livelihood source, livelihood strategy, economic institution and social security guarantee system in rural community. Based on these four aspects, the village with strong indigenous social institution is posses the livelihood system dominantly in agriculture and natural resource extraction, chosen livelihood strategy is more into multiple livelihoods in the form of multiple actors/straddling strategy, economic institution system is based on the collectivity to fulfill their food subsistence requirements. Their social security guarantee system is depends on social bonds like the patron-client pattern and communal activities. In the community with strong indigenous social institution, pace of social changes is relatively slow while in the community with the faded indigenous social institution and more “modernized”, the livelihood source of people is more dissimilar, both in agricultural and non agricultural based. It makes their livelihood strategy is also more divergent (agricultural intensification and extensification, multiple livelihood and migration). Economic institution system in this community is based on individual production activity which is market oriented (commercial). The form of community social security guarantee which developed besides patron-client bond between farmer and peasant which is getting more disappear, also depends on external institution (government program of poverty alleviation). The condition shows that pace of social changes is relatively faster in the modernized community